Testing convergence among attachment methods: Adult Attachment Interview, Relationship-Specific Attachment Scale, and Implicit Association Test - Petrowski, Katja; Imhoff, Roland; Schmalbach, Bjarne; Strauß, Bernhard; Banse, Rainer (Frontiers in Psychology, 2025)
Attachment theory describes the framework of how individuals relate in intimate relationships, including their confidence in receiving support and comfort from attachment figures. Three primary research directions, which have led to different methods, are used to investigate the attachment concept: developmental psychology, personality and socio-psychological research, and cognitive psychology. Conceptual differences and the need for convergence among these methods are of high interest to researchers. The present study explores convergence across different research traditions. The study involved 318 participants, including clinical and non-clinical groups matched for age and gender. Various psychometric instruments, including the Adult Attachment Interview (AAI), Relationship-Specific Attachment Scale (BBE), and Mother-Implicit Association Test (IAT), were used to measure attachment and related constructs. The hypothesized associations were investigated by structural equation models. Small correlations among the different methods were found, with stronger associations in the patient sample compared to that of the healthy individuals. The latent correlation was significant and small. Model fit indices indicated a much better fit in healthy controls. Even though there were moderate correlations among the different methods, the associations were generally stronger in the patient sample compared to that of the healthy individuals, even though the instruments were developed based on healthy individuals. The model fit was generally good in the healthy sample but less so in the patient sample. Due to the large differences in the theoretical and developmental background of the methods, it can be proposed that attachment representations may vary depending on the sample and method used.